Gear up for Calculus / Chew Yee Ming and Ch'ng Pei Eng - Chew, Yee Ming; Ch'ng, Pei Eng (Unit Penerbitan JSKM, 2020)
Scenario mathematics anxiety among university students becomes a popular issue around the world since 1970's. Ersozlu and Karakus (2019) stated 537 papers on mathematics anxiety had been published in various databases Web of Sciences between 2000 and 2018. Numerous studies about the causes of mathematics anxiety and its impact on the students' achievement in schools or college and their career choice had been investigated (Richardson & Suinn, 1972; Tobias & Weissbrod, 1980; Hembree, 1990; Ma & Kishor, 1997; Miller & Bichsel, 2004; Vitasari et.al. 2010; Estonanto, 2017). Mathematics anxiety has been discovered to discourage students at tertiary level from learning calculus and engineering mathematics confidently. Hence, it affects students' performance in calculus and they encounter the problem of utilizing calculus in the related engineering courses. Therefore, the issue arises the concern of all the educators to design the feasible of teaching and learning mathematics in calculus or engineering mathematics. Mastering the fundamental mathematics in calculus will ease the learning in different field. Hence, there are a few guidelines for students in calculus learning.